2021
DOI: 10.1051/e3sconf/202125701008
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Fuel Cell for Renewable Energies Generation from Manure Treatment

Abstract: In the process of society, high-density livestock farms have developed rapidly to satisfy the increasing demand for meat products. Excessive wastewater from the livestock farms accordingly brought multiple pollution and deteriorate the environment, with the wastewater containing abundant chemical energy regarded as futility. Furthermore, the ingredients of wastewater varied from distinct livestock farms as a result of different animal feeding habits. Consequently, it is a necessity for specific wastewater trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
(15 reference statements)
0
0
0
Order By: Relevance
“…During the 10 cycles, an average of 86.31 ± 2.18% COD removal efficiency was obtained. The water sample with a COD range of more than 1200 mg/L (which is the maximum COD range of integrated aquaculture systems such as fish poultry culture [33][34][35]) is mostly reduced to the permissible COD limit (250 mg/L) of the water sample within 36 h. Poultry chicken manure has a COD range of 450 mg/L and a BOD range of 480-500 mg/L [36]. Many researchers also found that the COD value of poultry litter and poultry droppings ranges up to 1200 mg/L [34].…”
Section: Performance Of Smfcmentioning
confidence: 99%
“…During the 10 cycles, an average of 86.31 ± 2.18% COD removal efficiency was obtained. The water sample with a COD range of more than 1200 mg/L (which is the maximum COD range of integrated aquaculture systems such as fish poultry culture [33][34][35]) is mostly reduced to the permissible COD limit (250 mg/L) of the water sample within 36 h. Poultry chicken manure has a COD range of 450 mg/L and a BOD range of 480-500 mg/L [36]. Many researchers also found that the COD value of poultry litter and poultry droppings ranges up to 1200 mg/L [34].…”
Section: Performance Of Smfcmentioning
confidence: 99%